PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) PADA MATERI PERTUMBUHAN DAN PERKEMBANGAN TUMBUHAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XII MIPA-1 SMA NEGERI 1 INDRAJAYA - Muhammad Gade (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2022)
This study aims to improve student learning outcomes in class XII MIPA-1 SMA Negeri 1 Indrajaya, Pidie Regency in the matter of plant growth and development by using the Problem Based Learning (PBL) model. This researchlasted for three months, from August to October 2019. The type of research used in this study was classroom action research which consisted of two cycles. The research subjects were students of class XII MIPA-1 SMA Negeri 1 Indrajaya, Pidie Regency, for the 2019-2020 school year, as many as 30 students. Data analysis used a comparative descriptive analysis technique by comparing the pre-cycle with the results achieved in each cycle, cycle I and cycle II. The percentage of completeness obtained in the first cycle was 76.66% with an average grade of 79.53 and increased in the second cycle to 93.33% with an average grade of 81.36. The conclusion from this research is that students are more enthusiastic and enthusiastic about participating in learning and applying the Problem Based Learning (PBL) model so that they can improve student learning outcomes for class XII MIPA-1 SMA Negeri 1 Indrajaya on plant growth and development materials at SMA Negeri 1 Indrajaya.keywords : Problem Based Learning (PBL), learning outcomes